Serangga dan mitos suku kaum jakun, Kampung Peta, Mersing Johor - Kemalok, Jai; Mohamed, Maryati (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
This study focuses on seeing insects from the mythical perspective of the Orang Asli tribe of Jakun, Kampung Peta, Mersing Johor. The existence of insects in the life of every ethnic in Malaysia has brought various elements of myths. Therefore, when combining myths and insects, it could be said that myth is a human way of understanding, expressing and linking insects to him/herself as well as a group/culture. The practice of using insects among ethnic groups in daily life is called etnoentomology. In this study, the insects studied are the butterfly (Lepidoptera), the odonates (Odonata) and the cicadas (Homoptera). This is because these insects are very popular in the community and have their own myths that are brought into the local culture of belief.